The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3390/en1010003
|View full text |Cite
|
Sign up to set email alerts
|

Waste Cooking Oil as an Alternate Feedstock for Biodiesel Production

Abstract: Abstract:As crude oil price reach a new high, the need for developing alternate fuels has become acute. Alternate fuels should be economically attractive in order to compete with currently used fossil fuels. In this work, biodiesel (ethyl ester) was prepared from waste cooking oil collected from a local restaurant in Halifax, Nova Scotia, Canada. Ethyl alcohol with sodium hydroxide as a catalyst was used for the transesterification process. The fatty acid composition of the final biodiesel esters was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(203 citation statements)
references
References 15 publications
6
187
2
8
Order By: Relevance
“…A. B. Chhetri et al [12] used 0.4%, 0.6%, 0.8%, 1.0% and 1.2% sodium hydroxide as a catalyst and observed that no reaction took place with the 0.4% NaOH. With catalyst concentrations of 0.6%, 0.8% and 1.0%, ester yields were approximately 50%, 94% and 40%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. B. Chhetri et al [12] used 0.4%, 0.6%, 0.8%, 1.0% and 1.2% sodium hydroxide as a catalyst and observed that no reaction took place with the 0.4% NaOH. With catalyst concentrations of 0.6%, 0.8% and 1.0%, ester yields were approximately 50%, 94% and 40%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…"Bio" represents its biological and renewable source, and "diesel" implies its use as a fuel on diesel engines [11]. Biodiesel is derived from renewable biomass sources thus it represents a closed carbon dioxide cycle (approximately 78%) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The high viscosity of oils make them not suited for direct use in diesel engines (Chhetri et al 2008); however, the conversion process (transesterification) allows the fuel viscosity and quality properties to shift and be comparable to those of petrodiesel. The results obtained from the samples with the highest biodiesel yield, all fell within the established limits of the ASTM (1.9-6-0 mm 2 /s), with a range between 5.7 and 5.8 mm 2 /s for B100 and 4.0-4.1 mm 2 /s for B20 samples.…”
Section: Viscositymentioning
confidence: 99%
“…They are biodegradable and insoluble in water, but soluble in organic solvents. Beyond their physical characteristics, the degree of denaturation of oil is affected by external factors such as the composition of the food, the frying temperature, exposure to oxygen, heating time and equipment used for frying (Chherti et al, 2008;Papageorgiou, 2009 The quality of waste cooking oils is expected to vary as it depends on the type of vegetable oil used, the different culinary practices and the systems for collection and storage of waste oils (Oliveros et al, 2007). Additionally, different oils are used under the same conditions -high and long exposure time frying temperatures -resulting to different characteristics (Papageorgiou, 2009).…”
Section: Waste Cooking Oilmentioning
confidence: 99%